Du primaire au second degré : les changements dans les - Amandine Charvet (Recherches en Éducation)
The upper primary schools of the Third Republic were the key establishments in the development of extended schooling. Created in the 1880s, they evolved a lot until their transformation into a middle school in 1941. Both in their organ-ization and in their programs, they underwent profound curricular changes. The actors, the levels of governance, but also the goals assigned to these schools were modified. Through the evolution of formal curricula, this article points out the school policies that shape curricular changes, but also the accumulation of « small » curricular changes that lead to a structural reform of the republican school system over time. This article also explores the boundaries of the notion of movement in and through education: working on curricular changes is particularly heuristic in order to question the evolution of studen’s « movement in the social space » of in relation to a hypothetical democratization of school success under the Third Republic.